ANALISIS PERKUATAN STRUKTUR AKIBAT PERUBAHAN FUNGSI RUANG DAN PENAMBAHAN JUMLAH LANTAI PROYEK RUMAH IBADAH YAYASAN BEREA KARAWACI, TANGERANG - Muhammad Rifqi; Yanuar Setiawan; Mursid Mursid (Politeknik Negeri Jakarta, 2023)
Aspects of building construction are impacted by population increase, technological advancements, and the growing needs of the community. Existing buildings may be converted to serve new purposes in an effort to meet space needs, particularly in key areas. The Barea Karawaci Foundation house of worship building, located in Tangerang City, has a structure that ranges in height from four to six stories, and its usage has changed from that of a shophouse to a place of worship. This is a choice since it is quicker to execute and more financially lucrative. After adding floors and modifying a room's purpose, the inspection of the existing structure is done using the ETABS program and manually computed against the fulfillment of the regulations' requirements. The same is done for reinforcement with concrete jacketing. By enlarging the beam's size from 200x400 to 400x500, adding 6D19 flexural reinforcement, and adding 10 shear reinforcement at intervals of 90 to 200 mm, the beam is strengthened. Column reinforcement is done by enlarging the column from 200x600 to 400x800, adding 18D13 and 14D13 reinforcement, and adding D10 shear reinforcement at distances ranging from 78 mm to 200 mm.